AAA237, an SKP2 inhibitor, suppresses glioblastoma by inducing BNIP3-dependent autophagy through the mTOR pathway - Yizhi Zhang; Wan Li; Yihui Yang; Sen Zhang; Hong Yang; Yue Hao; Xu Fang; Guanhua Du; Jianyou Shi; Lianqiu Wu; Jinhua Wang (Cancer Cell International, 2024)
Abstract Background Glioblastoma (GBM) is the most common brain tumor with the worst prognosis. Temozolomide is the only first-line drug for GBM. Unfortunately, the resistance issue is a classic problem. Therefore, it is essential to develop new drugs to treat GBM. As an oncogene, Skp2 is involved in the pathogenesis of various cancers including GBM. In this study, we investigated the anticancer effect of AAA237 on human glioblastoma cells and its underlying mechanism. Methods CCK-8 assay was conducted to evaluate IC50 values of AAA237 at 48, and 72 h, respectively. The Cellular Thermal Shift Assay (CETSA) was employed to ascertain the status of Skp2 as an intrinsic target of AAA237 inside the cellular milieu. The EdU-DNA synthesis test, Soft-Agar assay and Matrigel assay were performed to check the suppressive effects of AAA237 on cell growth. To identify the migration and invasion ability of GBM cells, transwell assay was conducted. RT-qPCR and Western Blot were employed to verify the level of BNIP3. The mRFP-GFP-LC3 indicator system was utilized to assess alterations in autophagy flux and investigate the impact of AAA237 on the dynamic fusion process between autophagosomes and lysosomes. To investigate the effect of compound AAA237 on tumor growth in vivo, LN229 cells were injected into the brains of mice in an orthotopic model. Results AAA237 could inhibit the growth of GBM cells in vitro. AAA237 could bind to Skp2 and inhibit Skp2 expression and the degradation of p21 and p27. In a dose-dependent manner, AAA237 demonstrated the ability to inhibit colony formation, migration, and invasion of GBM cells. AAA237 treatment could upregulate BNIP3 as the hub gene and therefore induce BNIP3-dependent autophagy through the mTOR pathway whereas 3-MA can somewhat reverse this process. In vivo, the administration of AAA237 effectively suppressed the development of glioma tumors with no side effects. Conclusion Compound AAA237, a novel Skp2 inhibitor, inhibited colony formation, migration and invasion of GBM cells in a dose-dependent manner and time-dependent manner through upregulating BNIP3 as the hub gene and induced BNIP3-dependent autophagy through the mTOR pathway therefore it might be a viable therapeutic drug for the management of GBM. Graphical Abstract